2014
DOI: 10.1364/oe.22.018513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica nanoparticles on electro-optical properties of polymer-stabilized liquid crystals

Abstract: We control the pretilt angle of liquid crystals (LCs) by simultaneously doping silica nanoparticles (SNs) and reactive monomers into the LC cell. Application of AC high voltage (ACHV) to the cell compels the lifting force and the facilitation of polar groups to move the SNs and monomers toward the substrate surface. Polymer networks and SNs are stabilized at the substrate surface after UV exposure, sustaining the LCs at high pretilt angles. The deposited SNs on the substrate surface increases the anchoring ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Similarly, the disadvantage of large driving voltages can be avoided by curing under an applied voltage. The findings on our PSLCs without nanoparticles essentially confirm previous observations on the effect of curing conditions on the performance of PSLCs [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, we succeeded in fabricating sufficiently small particles made of LiNbO 3 :Fe, which can be dispersed in the nematic liquid crystal E7 or in a polymer-stabilized liquid crystal based on E7.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the disadvantage of large driving voltages can be avoided by curing under an applied voltage. The findings on our PSLCs without nanoparticles essentially confirm previous observations on the effect of curing conditions on the performance of PSLCs [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In addition, we succeeded in fabricating sufficiently small particles made of LiNbO 3 :Fe, which can be dispersed in the nematic liquid crystal E7 or in a polymer-stabilized liquid crystal based on E7.…”
Section: Discussionsupporting
confidence: 90%
“…A voltage applied during the curing process was found in previous works to promote fast switching [ 31 ] or to imprint a bias effect on the switching behavior [ 32 ]. Combining both nanoparticle doping and polymer networks in LCs is currently a topical field of research [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a natural step forward is to combine all the three soft matter materials together, and particle-laden polymer-stabilized liquid crystals (PLPSLCs) indeed start to emerge as a research direction. The few existing studies [25][26][27][28][29][30][31][32][33] have demonstrated that PLPSLCs can not only decrease the threshold voltage and response times compared to PSLC systems [25][26][27] but also suppress particle-induced hysteresis effects and the formation of large particle aggregates thus increasing the device transmittance. 28 Moreover, a temperature independent threshold voltage has been reported for PLPSLCs in which nanoparticles have been incorporated into polymer strands.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Spatial director distribution in the LC cell depends strongly on director boundary conditions at the cell substrates, in particular, director pre-tilt angle and anchoring energy at the substrates. A series of methods have been developed to control the director boundary conditions, for example, irradiating alignment layers with ion beams, 20 doping the LC cells with nanoparticles, 21 or forming polymer structures on a substrate surface via electrostatic force 22,23 or UV light field. [24][25][26] In this present paper, we speculate that the photorefractive space-charge field may control the anchoring of the LC director at the cell substrates, and therefore affect the grating formation.…”
Section: Introductionmentioning
confidence: 99%